Siret revisited: The metals in the British Museum’s Siret collection - Murillo Barroso, Mercedes; Montero-Ruiz, Ignacio; Lackinger, Aaron; Wilkins, Neil; Hook, Duncan (SPAL - Revista de Prehistoria y Arqueología, 2024)
This paper presents the analytical study of the metal objects from the Siret Collection held by the British Museum. X-ray Fluorescence has been conducted to determine their elemental composition and by lead isotope analysis (by MC-ICP-MS) to determine their origin. We combine this new data with extant analyses to discuss and reinterpret the role of bronze alloys in Argaric society and the diversity of exploited mining resources.